L’École de Madrid et son devenir après la Guerre Civile - Eve Fourmont Giustiniani (Cahiers de Civilisation Espagnole Contemporaine)
The philosophic School of Madrid, consisting of several circles of disciples -José Gaos, María Zambrano, Julián Marías, Xavier Zubiri, Antonio Rodríguez Huéscar…-, orbiting the tutelary figure of José Ortega y Gasset, is generally confined to years of its peak, which correspond to those of the university reform conducted at the Faculty of Philosophy and Letters of the Central University under the Second Republic. The Spanish Civil War dissolved the rising philosophical tradition and dispersed its members into exile or in the cultural "desert" of Franco's Spain. Far from being the end of the School of Madrid, the war marks the division between the two branches of the orteguian philosophical legacy, which continues to grow through the thought of his disciples, despite various attempts of neutralization or political distorsion. The study of this double posterity is an essential step in understanding the history of Spanish ideas, including how the post-Franco transition was realized in the field of philosophy.